ANATOMICAL STUDY OF THE PRIMARY BRONCHI AND THE LUNG OF THE BEE-EATER BIRD ( MEROPS ORIENTALIS) - Nabeel Abd Murad Al-Mamoori (Basrah Journal of Veterinary Research)
The present study has been out to examine macroscopic structure of the primary bronchi and lung in Bee-eaters bird ( Merops orientalis) observed exist within the rib cage, the distal part of the trachea are divided into two primary bronchi (left and right) and the macroscopic appearance of the primary bronchi consists of a short tube extend caudally from syrinx to enter the proximal third of the visceral surface of the lungs through the hilus. The basic unit consisting of the primary bronchi are cartilaginous rings which takes - C - shape. The mean total length of left and right primary bronchi are (1.025 ± 0.15 cm) and (1.075 ± 0.14 cm); and the number of cartilaginous rings in left and right primary bronchi are ( 18.5 ± 0.50) and (18.5 ± 1.50). The lungs are small, pyramidal-shaped, unlobed, bright pink color, and surrounded by thin colorless membrane the pleura and the air sacs. The lung contains two surfaces (dorsal and ventral), two borders ( medial and lateral) and two extremities ( proximal and distal ). The mean total length, width and thickness of the right lung are (1.77 ± 0.17 cm), (0.95 ± 0.15 cm) and (0.4 ± 0.10 cm) while the mean total length, width and thickness of the left lung are (1.6 ± 0.15 cm ), ( 0.9 ± 0.14 cm ) and (0.37 ± 0.02 cm ).